The photoinduced β-carotene synthesis in Blakeslea trispora is dependent on WC-2A - Zheng, Qiang; Zhu, Kaili; Wang, Ke; Wang, Yi; Yu, Xiaobin; Luo, Wei (Frontiers in Microbiology, 2025)
β-Carotene, a high value-added natural pigment, is currently produced industrially in Blakeslea trispora. Although photoinduced carotenoid synthesis has been identified in some filamentous fungi, there are still relatively few studies focusing on B. trispora and its potential mechanisms. In this study, an integrated strategy—including correlation analysis of gene expression, bioinformatics analysis, protein interaction, and RNA interference—was adopted to elucidate photoinduced β-carotene synthesis in B. trispora. Light wavelength, intensity, and irradiation duration stimulated the transcription of photoreceptors [btwc-1 (a, b, c) and btwc-2 (a, b, c, d)] and carotenoid structural genes (carB and carRA). The transcription of photoreceptor genes showed significant or high correlation with carotenoid structural genes under continuous or short-term, high-intensity blue light irradiation. To elucidate the role of photoreceptors in carotenoid synthesis, the interaction between BTWC-1 and BTWC-2 was predicted. Furthermore, Glutathione S-Transferase (GST) pull-down assays showed that only BTWC-1C and BTWC-2A could interact to form complexes. Inhibition of btwc-2a expression under dark conditions did not affect β-carotene accumulation or the transcription of carB and carRA, but did reduce these parameters under blue light irradiation, indicating that btwc-2a mediates photoinduced β-carotene synthesis in B. trispora.